2010
DOI: 10.1007/s12039-010-0095-7
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene glycol: A recyclable solvent system for the synthesis of benzimidazole derivatives using CAN as catalyst

Abstract: Ceric ammonium nitrate (CAN) efficiently catalysed the synthesis of benzimidazole derivatives from o-phenylenediamine and aldehydes in PEG. This method provides a novel route for the synthesis of benzimidazoles in good yields with little catalyst loading. The recovery and the successful reutilization of the solvent system are also presented. Moreover, the easy set-up and purification tasks of this sustainable method make it appealing for bulk industry applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…It is the synthesized benzimidazole by reacting OPD with several aldehydes using a green solvent PEG400 and got good yields [45]. Scheme 14.…”
Section: Scheme 13 Synthesis Of Benzimidazole From Opd By Using Greementioning
confidence: 99%
“…It is the synthesized benzimidazole by reacting OPD with several aldehydes using a green solvent PEG400 and got good yields [45]. Scheme 14.…”
Section: Scheme 13 Synthesis Of Benzimidazole From Opd By Using Greementioning
confidence: 99%
“…Evaporation of the solvent gave the crude product, which was purified by column chromatography over silica gel (n-hexane:ethyl acetate, 5:1) to afford the corresponding benzimidazole. All of the compounds are known compounds which they were identified from their 1 H NMR spectroscopic data and by comparing their melting points with those reported in the literature [17][18][19][20]49,51,61,62,76,77].…”
Section: Typical Procedures For the Synthesis Ofmentioning
confidence: 99%
“…From literature found that, condensation of o-phenylene diamine with acids or aldehydes over homogenous catalysts such as copper acetate and lead tetra acetate [20], zinc acetate [21], ammonium chloride [22], zinc chloride [23], ammonium bromide [24], copper hydroxide [25], fluoroboric acid [26], boric acid [27], zinc triflate [28], ceric ammonium nitrate [29], and nickel acetate [30] were studied. In acylation reaction transition metals used as catalyst namely palladium [31], rhodium [32], and ruthenium [33].…”
Section: Introductionmentioning
confidence: 99%